Speaking - Collie, Joanne (Cambridge Skills for Fluency, 1991)
Develops oral fluency by focusing on topics that are personally revelant to steudents. The activities enable students to draw on their own life experience, feelings and cultural knowledge and develop their ability to expresss their ideas confidently and fluently even with pre-intermediate languaje skills.